ASSOCIATION BETWEEN THE VISCERAL ADIPOSITY INDEX AND HYPERTENSION-MEDIATED ORGAN DAMAGE IN THE COMMUNITY-DWELLING ELDERLY CHINESE: THE NORTHERN SHANGHAI STUDY. (April 2021) - Xu, Chong; Zhao, Song; Yu, Shikai; Chi, Chen; Fan, Ximin; Ji, Hongwei; Teliewubai, Jiadela; Zhang, Yi; Xu, Yawei
Abstract: Objective: The visceral adiposity index (VAI) was a novel indicator of visceral fat function and insulin resistance. Numerous studies had investigated that the VAI was associated with cardiovascular damage. However, few data are found on the correlation of VAI and hypertension-mediated organ damage (HMOD). We aimed to evaluate the association of HMOD with the VAI in the community-dwelling elderly Chinese population. Design and method: A cohort of 3363 elderly participants was recruited from June 2014 to August 2019. The relationship between the VAI and cardiometabolic risk factors was analyzed by Pearson's correlation. We used multivariable linear and logistic regression analysis to verify the relationship between the VAI and HMOD. Results: The VAI was significantly correlated with cardiometabolic risk factors (P < 0.001). In multivariable linear regression analysis, the VAI was associated with carotid-femoral pulse wave velocity (cf-PWV; b = 0.047, P = 0.024), ankle-brachial index (ABI; b = -0.003, P = 0.022), urine albumin to creatinine ratio (UACR; b = 3.893, P = 0.008), estimated glomerular filtration rate (eGFR; b = -0.526, P = 0.003). After the VAI was put into the multivariable logistic regression model, higher VAI was significantly related to cf-PWV > 10m/s (OR = 1.50, [95% CI, 1.12–2.00]; P = 0.006), micro-albuminuria (OR = 1.32, [95%CI, 1.03–1.70]; P = 0.019) and chronic kidney disease (OR = 1.56, [95% CI, 1.03–2.37]; P = 0.031). Conclusions: Higher VAI might be related to an increased risk of arterial stiffness and kidney damage. The VAI may be used as a tool to evaluate early HMOD in the elderly Chinese population.